2019
DOI: 10.1002/lt.25626
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Encephalopathy Is Reversible in the Long Term After Liver Transplantation

Abstract: Cognitive dysfunction caused by hepatic encephalopathy (HE) improves within the first year after liver transplantation (LT). However, cognitive restitution seems to be incomplete in a subset of patients and after LT a new‐onset cognitive decline was described. Data about the longterm development of cognitive function after liver transplantation (LT) are sparse. This prospective study analyzed whether a history of hepatic encephalopathy (HE) before LT had an impact on the longterm outcome of cognitive function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…It is very challenging to give accurate clinical diagnosis before overt symptoms set in, thus, leading to a decrease in the quality of life and survival time ( Bajaj, 2008 ; Wijdicks, 2016 ). Learning ability of HE is not completely reversible and new cognitive decline occurs after treatment in some patients ( Riggio et al, 2011 ; Hopp et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is very challenging to give accurate clinical diagnosis before overt symptoms set in, thus, leading to a decrease in the quality of life and survival time ( Bajaj, 2008 ; Wijdicks, 2016 ). Learning ability of HE is not completely reversible and new cognitive decline occurs after treatment in some patients ( Riggio et al, 2011 ; Hopp et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies assessed cognition on these two groups of patients after LT and were included in a subsequent analysis. Of those, three studies (Sotil et al, 2009;Garcia-Martinez et al, 2011;Hopp et al, 2019) were included only in the post-LT due to lack of sufficient pre-LT data concerning neuropsychological tests scores for patients with and without a history of OHE specifically.…”
Section: Aim and Scopementioning
confidence: 99%
“…The post-LT analysis included six studies totaling 151 patients with and 156 patients without a history of OHE. For studies evaluating the effect of overt HE after LT, the time after LT varied from 6 months (Acharya et al, 2017) to up to 5 years (Hopp et al, 2019).…”
Section: Meta-analysismentioning
confidence: 99%
“…Whether neurological complications observed in LT recipients are residual symptoms from a history of HE (pre-LT) or newly developed perioperatively (HE-influenced) or related to a comorbidity is difficult to define accurately. Having said this, a recent study reported a recovery of brain function in patients followed-up long-term (>5 years) post-LT. 150…”
Section: Impact Of Hepatic Encephalopathy On Neurological Outcome Folmentioning
confidence: 99%